On‐site economic evaluation of soil conservation practices in Honduras - Carcamo, J. A. (Wiley, 1994)
Factors affecting the cost to the farmer of employing soil erosion reduction strategics are examined for the steep hillsides near Tegucigalpa, Honduras. Linear programming and MOTAD are used to examine these factors. Results indicate that some modest reductions in erosion can be achieved at little cost to the farmer by reorganizing production, switching rotations, and using contour plowing. These modest reductions still lead to extremely high rates of erosion. Sharper reductions may be achieved at progressively higher costs as erosion control structures are constructed and acreage is left fallow. There is a high cost to the farmer of reducing erosion to ‘sustainable’ levels. A consistent tradeoff emerges between levels of soil conservation, income, and risk; erosion reduction efforts lead to lower incomes and higher risk. The analysis of likely benefits to farmers for erosion reduction shows that even under assumptions of very high yield losses from soil erosion, optimal farm plans still lead to high rates of soil loss, implying a need for policies that internalize externalities if off‐farm damages are to be minimized.